α-Hemihydrate calcium sulfate/n-hydroxyapatite combined with metformin promotes osteogenesis in vitro and in vivo - Liu, Sirui; Fu, Haojie; Lv, Yan; Jiao, Jing; Guo, Runying; Yang, Yanyu; Dong, Wenhang; Mi, Hongyan; Wang, Meiyue; Liu, Mengzhe; Li, Rui (Frontiers in Bioengineering and Biotechnology, 2022)
The purpose of this study is to examine the effects of loading different concentrations of metformin onto the α-hemihydrate calcium sulfate/nano-hydroxyapatite (α-CSH/nHA) composite. Material characteristics, biocompatibility, and bone formation were compared as a function of metformin concentration. X-ray diffraction results indicated that metformin loading had little influence on the properties of the composite. The hemolytic potential of the composite was found to be low, and a CCK-8 assay revealed only weak cytotoxicity. The osteogenic ability of MC3T3-E1 cells, as revealed by alkaline phosphate and alizarin red staining, real-time PCR, and western blotting, was enhanced by the composite material, and the optimal concentration was found to be 500 µmol. RNA sequencing results showed that the expression of osteogenic-related genes was enhanced by treatment with the metformin-loaded composite, and the Wnt and Hippo signaling pathways were significantly altered. Micro-computed tomography, hematoxylin and eosin (H&E) staining, Masson staining, and immunohistochemical staining were used to determine the effectiveness of the composite as a scaffold in a rat skull defect repair model. The composite material loaded with 500 µmol metformin had the strongest osteoinduction ability under these conditions. These results are promising for the development of new methods for repairing craniofacial bone defects.